A Review on the Concerns and Awareness Related to Menstrual Cycle in Women - R, Kumar; S, Kumar; Akanksha, (Medical Science: Trends and Innovations Vol. 13, 2025)
The shedding of the uterus lining due to no fertilization of the ovum leading to bleeding is known as menstruation. As a woman plays a vital role in reproduction and other natural, social processes, it is necessary for her to take good care of herself and her body. This article delves into the intricate interplay between the menstrual cycle and various dimensions of female health. Investigating the mental, emotional, and social aspects of self-worth, the present review seeks to uncover the multifaceted nature of this biological phenomenon. Through an amalgamation of extensive literature review and empirical analysis, the study explores how hormonal fluctuations during menstruation contribute to physiological changes, potentially affecting energy levels, exercise routines, and dietary habits. It explores mental health concerns by investigating the potential links between hormonal fluctuations and cognitive processes. Emotional well-being is scrutinized, considering the influence on mood, stress levels, and overall emotional stability. Social dynamics are examined to understand how menses impact interpersonal relations, communication patterns, and societal attitudes and perceptions. Psychological dimensions are explored, seeking insights into the broader implications of menstruation on a female's sense of self and identity. Additionally, it scrutinizes implications on daily activities such as work, education, and leisure pursuits. The physical implications of menstruation have been analysed, incorporating nutritional measures to assess the impact of energy levels, dietary habits, and overall physical health. Moreover, by integrating nutritive measures, its purpose is to offer practical insights that may inform holistic approaches to female health, fostering awareness and support systems tailored to the diverse needs of women as they navigate the challenges and opportunities associated with menstruation. It has been found that both mental state and well-being and menstrual variations are interrelated. The changes in hormones during periods can affect how a female thinks and feels mentally or physically. Additionally, Menstrual difficulties can significantly impact their curricular and co-curricular achievements, parameters related to attendance and societal lifestyle. Again, menstruation can impact the body’s nutrient needs. The blood loss during menstruation leads to decreased iron levels, resulting in iron deficiency and anaemia if not properly addressed through dietary intake or supplementation. In conclusion, consuming a well-balanced diet with adequate nutrients can help alleviate PMS symptoms. An anti-inflammatory diet can help manage endometriosis pain and inflammation. Including foods rich in antioxidants such as berries, leafy greens, and turmeric, along with omega-3 fatty acids from fish, walnuts, and flaxseeds, can be beneficial. Avoiding processed meats, excessive red meat, and high-fat dairy products is recommended.